Sensacja w służbie propagandy — „Biblioteczka Ziem Zachodnich” - Paweł Kaczyński (Literatura i Kultura Popularna)
‘Biblioteczka Ziem Zachodnich’ [The Western Territories Library] was a series published in 1960–1971 by the ‘PAX’ Publishing Institute, in which 49 entries were published. Those were novels, diaries, reportages and popular science monographs. Most of the contributors were littleknown writers and journalists affiliated with the PAX Association, although two reportages by Melchior Wańkowicz were also published. Propagandistic justifications of Poland’s rights to the so-called Recovered Teritories and recollections of the ‘eternal’ struggle of Poles against Germanic pressure (mainly via a World War II setting or background) were the main purposes of the series. Emphasis was also placed on the threats from the West Germany, which was presented as a continuation of the Third Reich. Among other things, the narrative means typical of crime fiction were used to achieve these propaganda purposes. Themes of espionage and mystery, criminal investigations, the search for hidden documents or valuables, or prosecution of Nazi criminals can be found in many works. All these ‘tricks’ serve as entertainment, attracting the reader’s attention, but this function is subordinated to the main aim — presenting the image of the world and Polish–German relations in accordance with the official propaganda line.